Efforts to Increase the Number of New Students at Private Universities at the LMII Indonesia Medan High School of Economics during the Covid-19 Pandemic Period Hit the World with the Implementation of Strategic Management - Lumbanraja, Togu Harlen; Sitanggang, HD. Melva (Journal Of Accounting Management Business And International Research, 2023)
Increasing the number of new students at each tertiary institution is very important, especially during the Covid-19 pandemic, the number of students decreased, where the number of students is an indicator of the success of tertiary management. So that in situations like this, what is also called strategic management is needed. Strategic management in the form of planning, organizing, acting and controlling, all of which are functions rather than management itself, must be used to ensure organizational goals are achieved with efficiency and effectiveness. The research design used was based on research and development and in this study it could only be at the product design stage which resulted in a planning strategy to increase the number of students at the LMII Indonesia Medan College of Economics. The purpose of this study was to determine the implementation of strategic management applied at the LMII Indonesia Medan College of Economics in increasing the number of new students starting from strategy formulation, strategy implementation, and strategy evaluation. This research is a qualitative research using data collection instruments through interviews, observation, FGD and studying documents. Data analysis was carried out using SWOT analysis to analyze internal and external factors such as school climate, weaknesses, opportunities, and enrollment to develop strategies to increase the number of quality new students. The results of the SWOT analysis show that you are in a Strength Opportunity (SO) position, using an aggressive strategy by utilizing the internal network to pursue the goal of capturing certain opportunities from certain external networks. The suggested competitive strategies for planning educational institutions or schools are: 1) Promotion through online and offline media; 2) Organize high school/vocational school olympiad competitions at the local level; 3) Cooperation with the local village government; 4) Standard Lecturers have met the qualifications of Masters graduates in their respective Lecturer fields, 5) With high fighting spirit or commitment in teaching service for Lecturers, 6) Fairly complete facilities and infrastructure, 7) Good cooperation with the community environment, 8 ) waiver of registration fees, 9) giving rewards/awards to academics who have successfully registered new students; ) ease of registration process; and 10) providing scholarship assistance to underprivileged students.